2011
DOI: 10.1108/01443581111096178
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of fiscal policies in Portugal

Abstract: PurposeThis paper seeks to estimate the long‐term effects on output of different fiscal policies in Portugal.Design/methodology/approachResults are obtained from accumulated impulse response functions associated with unrestricted VAR models that include several public spending and taxation variables in addition to output.FindingsEmpirical results suggest that the effects of fiscal policies are within the Keynesian paradigm for public investment and direct taxation. In turn, non‐Keynesian effects dominate in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…By using the structural VAR approach, Blanchard and Perotti (2002) discovered that government spending has a positive effect, however, taxation has a negative effect, on output. Besides that, Marvão Pereira and Roca-Sagalés (2011) who studied the effect of fiscal policies at the aggregate and disaggregate level using the Cholesky decomposition for shock identification focussing on Portugal found results that were consistent with Blanchard and Perotti (2002). A number of researchers, such as Jiranyakul and Brahmasrene (2007), Chatziantoniou, Duffy, and Filis (2013), Mutuku and Koech (2014), Ćorić, Šimović, and Deskar-Škrbić (2015) and Nursini (2017), also found that fiscal policy has a positive relationship with output.…”
Section: Literature Reviewsupporting
confidence: 63%
“…By using the structural VAR approach, Blanchard and Perotti (2002) discovered that government spending has a positive effect, however, taxation has a negative effect, on output. Besides that, Marvão Pereira and Roca-Sagalés (2011) who studied the effect of fiscal policies at the aggregate and disaggregate level using the Cholesky decomposition for shock identification focussing on Portugal found results that were consistent with Blanchard and Perotti (2002). A number of researchers, such as Jiranyakul and Brahmasrene (2007), Chatziantoniou, Duffy, and Filis (2013), Mutuku and Koech (2014), Ćorić, Šimović, and Deskar-Škrbić (2015) and Nursini (2017), also found that fiscal policy has a positive relationship with output.…”
Section: Literature Reviewsupporting
confidence: 63%